Designing Novel Waterborne Polylactic Acid Coatings for Food Packaging Applications Including Polyvinyl Alcohol as Stabilizer - Rojas-Sepulveda, A; Velasquez, E (Elsevier Ltd, 2025)
Waterborne polylactic acid (PL) coatings were successfully prepared through a two-step emulsification-evaporation process by using polyvinyl alcohol (Pv) solutions as stabilizer and sodium dodecyl sulfate (SDS) as surfactant. First, various emulsions of PL were carried out by mixing a 18 % (w/v) PL solution in ethyl acetate with diverse volumes of Pv aqueous solutions at concentration ranging between 2 % and 11.6 % (w/v). The emulsions developed with low concentrated Pv solutions (2 % w/v) were all discarded due to lack of stability. From the stable solutions, PL dispersions were prepared by ethyl acetate evaporation. By modifying Pv concentration and the volume of stabilizer, six PL dispersions were successfully obtained with PL/Pv ratio varying from 42/58–70/30. Both the PL emulsions and dispersions were rheologically characterized and the latter were used to obtain cast composite films that were characterized through their physical and technological properties. The viscosity of the developed coating dispersions were mainly governed by Pv concentration. FTIR analysis of composite films revealed interactions between chemical groups of both polymers that were confirmed by thermogravimetric analysis. Both the water vapor sorption and the oxygen permeability (PO2) of composite films were highly affected by the Pv concentration and the relative humidity (RH). The reduction of PO2 was more noticeable at the highest Pv ratio and the lowest RH. Although, PO2 of composite films increased as RH increased, their oxygen barrier was between 15 and 5 times better than control PL film. © 2025 Elsevier Ltd